A monoclonal antibody-Pseudomonas toxin conjugate that specifically kills multidrug-resistant cells. - FitzGerald, D J (1987)
One form of multidrug resistance is due to the expression of a 170-kDa energy-dependent drug efflux pump called P-glycoprotein in the plasma membranes of human cancer cells. We have prepared conjugates of Pseudomonas toxin with the anti-P-glycoprotein monoclonal antibody MRK-16. These anti-P-glycoprotein-toxin conjugates specifically kill multidrug-resistant human KB cells. Similar conjugates could be useful in cancer therapy to reduce or eliminate multidrug-resistant tumor populations in tumors intrinsically resistant to chemotherapy or in populations that become resistant during combination chemotherapy.